Financial Performance Analysis of Shares Returns in Cosmetics and Household Purposes Companies (Studies on companies listed on the Indonesian Stock Exchange) - Rajindra Rajindra; Guasmin Guasmin; Burhanuddin Burhanuddin (Universitas Muhammadiyah Palu, 2021)
The assumption underlying this research is how investors invest in cosmetics and household goods companies listed on the Indonesia Stock Exchange (IDX) with the availability of information to assess an investment. The purpose of this study is to determine and analyze financial performance as measured from the aspects of liquidity, solvency, and profitability simultaneously have a significant effect on stock returns in cosmetic and household goods companies listed on the Indonesian Stock Exchange and to find out and analyze financial performance as measured by aspects of liquidity, solvency, and profitability partially have a significant effect on stock returns in cosmetic and household goods companies listed on the Indonesian stock exchange. The data obtained from the research object was collected using documentation techniques, namely data collection, classifying, and using sequential data in notes and reports, especially financial statements related to research.